2007
DOI: 10.2174/156800907781386588
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and DNA Repair - Potential Molecular Mechanisms of Action

Abstract: At its most fundamental, cancer is a genetic disease in the sense that the primary events in tumorigenesis involve damage to the genome. The genome is subject to damage continuously from both exogenous agents and endogenous processes but this becomes functionally important only if the damage is not detected and resolved in a timely and effective manner. In mammals there are 5 DNA repair pathways, encoded by approximately 150 genes, which appear to have arisen early in evolution and which are highly conserved. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…Moreover, other micronutrients not monitored during this study, such as Zn and Se, may influence epigenetic modifications, e.g., via DNA methylation [43,44]. In addition, there are data indicating that food components and/or nutritional status influences the DNA repair process and thereby affect the response to DNA damage [45]. Nevertheless, none of the dietary factors monitored in this study were associated with fMN, with the exception of the exclusion of fish and meat and the inclusion of protein-rich vegetarian foods in the vegetarian group.…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, other micronutrients not monitored during this study, such as Zn and Se, may influence epigenetic modifications, e.g., via DNA methylation [43,44]. In addition, there are data indicating that food components and/or nutritional status influences the DNA repair process and thereby affect the response to DNA damage [45]. Nevertheless, none of the dietary factors monitored in this study were associated with fMN, with the exception of the exclusion of fish and meat and the inclusion of protein-rich vegetarian foods in the vegetarian group.…”
Section: Discussionmentioning
confidence: 93%
“…To date there have been some descriptive studies of epigenetic changes in the aging brain, and in the brain of Alzheimer patients, but little is known about the role of epigenetic processes in causing the cellular dysfunction, which is characteristic of neurodegenerative disorders (24, 33). Our study was one of the first to investigate how early life nutritional interventions alter oxidative damage and promoter methylation of BER‐related genes and to determine effects on neuronal DNA repair.…”
Section: Discussionmentioning
confidence: 99%
“…Se-induced activation of p53 is also dependent on the BRCA1 protein in recombinational repair, which is frequently mutated in familial breast cancer (55). It also was reported that Se inhibited DNA-binding activity of transcription factors such as AP-1, NF-kB, SP-1, and SP-3, as well as the DNA-repair proteins XPA in the NER pathway and formamidopyrimidine DNA glycosylase (FPG) in the BER pathway (27,76,131,195). These data imply that Se may reduce cancer incidence through modulating DNA repair, redox status of cells, and the cellular transcriptional response to oxidative stress.…”
Section: A Dietary Antioxidantsmentioning
confidence: 98%